2008
DOI: 10.1111/j.1365-294x.2008.03756.x
|View full text |Cite
|
Sign up to set email alerts
|

High population differentiation and unusual haplotype structure in a shade‐intolerant pioneer tree species, Zanthoxylum ailanthoides (Rutaceae) revealed by analysis of DNA polymorphism at four nuclear loci

Abstract: Differences in demographic history, life-history traits, and breeding systems affect nucleotide variation patterns. It is expected that shade-intolerant pioneer tree species have different patterns of genetic polymorphism and population structure than climax species. We studied patterns of nucleotide polymorphism at four putative starch pathway loci (agpSA, agpSB, agpL, and GBSSI) in Zanthoxylum ailanthoides, a shade-intolerant pioneer tree species that occupies forest gaps in warm-temperate forests of East As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…The mean divergence between A. obovata and L. formosana is low, about 3.45 and 1.51% according to the two genes used in this study (Table S3). The level of divergence is comparable with that of two sister species within a single genus (Sang et al 1995;Zhou et al 2007;Kamiya et al 2008). The low level of divergence between Liquidambar and Altingia may indicate that the ease of hybridization between them is equivalent to intrageneric hybridization in other plant groups.…”
Section: Discussionmentioning
confidence: 73%
“…The mean divergence between A. obovata and L. formosana is low, about 3.45 and 1.51% according to the two genes used in this study (Table S3). The level of divergence is comparable with that of two sister species within a single genus (Sang et al 1995;Zhou et al 2007;Kamiya et al 2008). The low level of divergence between Liquidambar and Altingia may indicate that the ease of hybridization between them is equivalent to intrageneric hybridization in other plant groups.…”
Section: Discussionmentioning
confidence: 73%
“…A part of the putative candidate selected gene, agpL, suggested by Kamiya et al (2008) was newly sequenced for five samples each from four populations selected on the basis of their locations (populations with asterisks in Fig. 1).…”
Section: Dna Sequencingmentioning
confidence: 99%
“…It is distributed throughout the east coast of Asia from the Philippines to the main island of Japan and is often found in warm-temperate evergreen oak forests below 1,500 m (Horikawa 1972). We investigated nucleotide sequence variation at four nuclear loci in a limited sample of this species from southern Japan (Kyushu) and observed remarkably high levels of genetic differentiation among populations and low haplotype number (Kamiya et al 2008), both of which were different from those found in many other trees thus far studied (González-Martinez et al 2006;Savolainen and Pyhäjärvi 2007). Furthermore, one of the four loci, agpL, encoding the large subunit of the heterotetrameric enzyme, AGPase, had remarkably low nucleotide diversity (nearly no variation) compared with the other three loci, although the divergence of agpL from that in its sister species was not low.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations